NOVEL ACCURATE NANOSATELLITE ATTITUDE ESTIMATION AND CONTROL ARCHITECTURE BASED ON MAGNETIC DIPOLE MOMENT AND ACTUATOR FAULT COMPENSATION (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Nanosatellites are increasingly considered an effective alternative to traditional solutions for Earth observation missions from space. The attitude determination and control system (ADCS) is one of the key subsystems of a nanosatellite, critical for the mission’s success. This paper investigates the design of an Extended Kalman filter (EKF) for a nanosatellite attitude determination along with the residual magnetic moment and the actuator fault compensation. The proposed architecture relies on a heuristic extended Kalman filter (HEKF) and adaptive proportional-derivative (APD) controller. The optimized filtering system searches for the best measurement covariance and process noise matrices to track the best estimation of the attitude and residual magnetic moment disturbance. In addition, the APD controller, based on an observer, is designed to cope with uncertainties in actuator failure and provide a reliable attitude control for the nanosatellite. The investigated attitude filtering and control scheme is examined through numerical simulation to determine whether it offers benefits in terms of performance and convergence behavior.
Keywords: Nanosatellite; Varying residual magnetic moment (RMM) compensation; Extended Kalman filter (EKF); Particle swarm optimization (PSO); Actuator faults; Adaptive proportional derivative (APD)